MEDIA PEMBELAJARAN INTERAKTIF BAHASA INDONESIA DI KELAS IV SD NEGERI 42/IV KOTA JAMBI: Interactive Learning Media, Indonesian Language, Waterfall Method, Learning Features, User Satisfaction, SD Negeri 42/IV Kota Jambi. - Megawati, Merti; Puspitorini, Sukma; Setya Ardifa, Febri (JURNAL AKADEMIKA, 2025)
This study aims to develop and evaluate the effectiveness of interactive learning media for the Indonesian language subject in Grade IV at SD Negeri 42/IV Kota Jambi using the Waterfall method. The Waterfall method was applied through steps like needs analysis, design, development, testing, and maintenance, ensuring each step was done in an organized and systematic way. The interactive learning media was created using Macromedia Flash 8 and includes features like learning materials, animations, interactive quizzes, and interesting visuals to help students understand the content better. After development, the media was tested on 20 Grade IV students. The test results showed that 95% of the students were "Very Satisfied" with the use of this learning media, which means it not only helps improve understanding but also makes learning more fun and engaging for students. In conclusion, this interactive learning media has the potential to be an effective and enjoyable tool for teaching Indonesian in elementary schools.